Recovering Hidden Responder Groups in Individuals Receiving Neurofeedback for Tinnitus - Riha, Constanze; Güntensperger, Dominik; Kleinjung, Tobias; Meyer, Martin (Frontiers in Neuroscience, 2022)
The widespread understanding that chronic tinnitus is a heterogeneous phenomenon with various neural oscillatory profiles has spurred investigations into individualised approaches in its treatment. Neurofeedback, as a non-invasive tool for altering neural activity, has become increasingly popular in the personalised treatment of a wide range of neuropsychological disorders. Despite the success of neurofeedback on the group level, the variability in the treatment efficacy on the individual level is high, and evidence from recent studies shows that only a small number of people can effectively mod-ulate the desired aspects of neural activity. To reveal who may be more suitable, and hence benefit most from neurofeedback treatment, we classified individuals into unobserved subgroups with similar oscillatory trajectories during the treatment and investigated how subgroup membership was predict-ed by a series of characteristics. Growth mixture modelling was used to identify distinct latent sub-groups with similar oscillatory trajectories among 50 individuals suffering from chronic subjective tinni-tus (38 male, 12 female, mean age = 47.1  12.84) across 15 neurofeedback training sessions. Further, the impact of characteristics and how they predicted the affiliation in the identified subgroups was evaluated by including measures of demographics, tinnitus-specific (Tinnitus Handicap Inventory) and depression variables, as well as subjective quality of life subscales (World Health Organization – Quality of Life Questionnaire), and health-related quality of life subscales (Short Form-36) in a logistic regres-sion analysis. A latent class model could be fitted to the longitudinal data with a high probability of cor-rectly classifying distinct oscillatory patterns into 3 different groups: Non-Responder (80%), Responder (16%), and Decliner (4%). Further, our results show that the health-related well-being subscale of the Short Form-36 questionnaire was differentially associated with the groups. However, due to the small sample size in the Responder group, we are not able to provide sufficient evidence for a distinct re-sponder profile. Nevertheless, the identification of oscillatory change-rate differences across distinct groups of individuals provides the groundwork from which to tease apart the complex and heteroge-neous oscillatory processes underlying tinnitus and the attempts to modify these through neurofeed-back.